The Implementation of Fatḥ Kutub al-Turāts in the Religious Understanding of Students at Modern Islamic Institution Darussalam Gontor For Girl Campus 4 - A. Muttiara Wijayanto AK; Sitti Mania; M. Rusdi T (At-Ta'dib, 2022)
The study of Islamic classical books is crucial in the process of religious understanding. Gontor is one of the pesantren that still maintains the study of Islamic classical books with different methods. This study aims to explain the implementation system of Fatḥ kutub al-turāts in the religious understanding of students at Modern Islamic Institution Darussalam Gontor For Girl Campus 4 South Konawe, the obstacles in its implementation, and the efforts to overcome these obstacles. This research is a descriptive qualitative one that uses observation, interview, and documentation to obtain the whole data. The result of this study shows that Fatḥ kutub al-turāts is an activity of classic books study that aimed religious understanding of the students, that involves student, teachers, facilities, etc. in such procedure. This activity plays an important role in students’ religious understanding in terms of its material and its process that applied a student-centered learning approach, strategies, and methods that allow them to understand the religious materials independently, which is indicated by students’ ability to determine the main ideas, to give an example, to conclude the result of their study, and then convey it in their own language in the form of papers and presentations. The obstacles to this activity are the short duration of implementation, students’ difficulty in studying independently, and classic books that are used are wanting in number and variety. The efforts to overcome these obstacles are by providing briefings, division tasks in a team, escorting students intensively, and coordinating in the procurement of books.